2015
DOI: 10.1016/j.bcp.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Covalent adduct formation between the plasmalogen-derived modification product 2-chlorohexadecanal and phloretin

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
(83 reference statements)
1
7
0
Order By: Relevance
“…To determine whether PHL could cross the rat bloodbrain barrier (BBB), the level of PHL in the brain was determined by a liquid chromatography-tandem mass spectrometry (LC-MS/MS) following the intragastrical administration of 50 mg/kg PHL. We found that the peak level of PHL was detected in the brain at 60 min (Figure 1B), suggesting that PHL can cross the rat blood-brain barrier (BBB), which was consistent with a previous report in mice [25].…”
Section: Phl Attenuates the Cms-induced Depressive-like Behaviors In ...supporting
confidence: 92%
“…To determine whether PHL could cross the rat bloodbrain barrier (BBB), the level of PHL in the brain was determined by a liquid chromatography-tandem mass spectrometry (LC-MS/MS) following the intragastrical administration of 50 mg/kg PHL. We found that the peak level of PHL was detected in the brain at 60 min (Figure 1B), suggesting that PHL can cross the rat blood-brain barrier (BBB), which was consistent with a previous report in mice [25].…”
Section: Phl Attenuates the Cms-induced Depressive-like Behaviors In ...supporting
confidence: 92%
“…Moreover, these fatty acid species have been detected as being free or esterified. Furthermore, emerging studies indicate unique biological effects of Cllipids in stimulating inflammation, promoting cell-death, and dysfunction in eNOS-signaling (19,21,23,(26)(27)(28)(29)(30), which are also all features of post-Cl 2 gas toxicity (4,15). Cl-lipids are predicted to be formed via direct reactions of Cl 2 gas with the vinyl ether bond in plasmalogens, leading us to hypothesize that these species may be mediators of post-Cl 2 gas toxicity.…”
Section: Measurement Of Glutathione Adducts Of 2-cl-pald and 2-cl-mentioning
confidence: 99%
“…2-ClFALD has been shown to accumulate in the lungs of chlorine gas-exposed mice, infarcted rat myocardium and human aorta [4,5,9]. 2-ClFALD has been shown to cause cytotoxicity in several cell lines [10][11][12]. It is likely that the 2-ClFALD modification of proteins is responsible for many of the biological properties of 2-ClFALD.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloperoxidase-derived 2-ClFALD and 2-ClFA are suggested to be involved in endothelial dysfunction, neutrophil chemotaxis, NETosis and vascular tone [6][7][8][9]. Additionally, the Ford lab and other labs have shown that 2-ClFALD and 2-ClFA cause cell toxicity [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%